(untitled) (LEARNing Landscapes, 2021)
The purpose of this paper is to support mathematics teacher educators (MTEs) to prepare their graduate students in becoming MTEs by creating a learning environment to develop epistemological stances. I present the components of my graduate seminar taught in a Practice-based Teacher Education program. The seminar aims to support graduate students to develop their stances and to address the “practice-theory” tension that exists between university courses and the work of teaching. I provide an overview of the class activities and present assignments that support graduate students in becoming MTEs.